PENGEMBANGAN KARAKTER SISWA MELALUI KEGIATAN EKSTRAKURIKULER PRAMUKA DI MIN 1 JEPARA - Faizah, Nur; Rois, Nur; Mahalli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the role of Scout extracurricular activities in the development of student character in MIN 1 Jepara. The background of this research departs from the challenges of students' character in the digital era, such as declining discipline and social sensitivity. The method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study show that structured and routine Scout activities are able to shape student character values, especially discipline, responsibility, independence, cooperation, and social concern. The process of internalizing values is carried out through an approach of habituation, example, and strengthening the meaning of activities, with support from the head of the madrasah and the coach. The main obstacle faced is the limited facilities and training of coaches. Nevertheless, Scout activities have proven to be an effective instrument of character education in Islamic-based ibtidaiyah madrasas. This research contributes to strengthening the character development model in basic education institutions and becomes a practical reference in optimizing scouting activities